(untitled) (Journal of the College of Basic Education, 2025)
In this work, the prepared ZnO nanostructured films by chemical bath deposition at a reaction temperature of 70°C without any post-treatment. Zinc nitrate hexahydrate (Zn(NO3)2.6H2O) was used as a synthetic precursor, and the preparation of ZnO nanostructures was achieved within a few hours. The obtained ZnO nanostructures were characterized by X-ray diffraction (XRD, AFM, UV). The ZnO layer had a hexagonal structure, the grain size was between 22 nm, the transmission layer was 90%, and the morphology and optical properties of the layer were detected.